2016
DOI: 10.3389/fphys.2016.00325
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Properties of the Strawberry (Fragaria ananassa) against Carbon Tetrachloride-Induced Hepatotoxicity in Rats Mediated by Anti-Apoptotic and Upregulation of Antioxidant Genes Expression Effects

Abstract: The strawberry (Fragaria ananassa) has been extensively used to treat a wide range of ailments in many cultures. The present study was aimed at evaluating the hepatoprotective effect of strawberry juice on experimentally induced liver injury in rats. To this end, rats were introperitoneally injected with carbon tetrachloride (CCl4) with or without strawberry juice supplementation for 12 weeks and the hepatoprotective effect of strawberry was assessed by measuring serum liver enzyme markers, hepatic tissue redo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 59 publications
3
21
0
Order By: Relevance
“…These findings are very important because in pancreas, a study found that long‐term to high fat promotes oxidative stress followed by detrimental to Beta cells, producing activation of apoptotic ways (Zhao et al., ). Moreover, the liver plays an important role in complex metabolism like glycogen storage, lipid and protein synthesis, and detoxification (Hamed et al., ), for this reason, impairment liver function can lead to increase oxidative stress (Hamed et al., ). In our study, HFD increased the TBARS and carbonyls levels, whereas the NSE and UViSE extracts reduced these markers of oxidative damage; thus, ours extracts protect to the liver against oxidative damage, but unfortunately the effect of UViSE on protein oxidation was not significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are very important because in pancreas, a study found that long‐term to high fat promotes oxidative stress followed by detrimental to Beta cells, producing activation of apoptotic ways (Zhao et al., ). Moreover, the liver plays an important role in complex metabolism like glycogen storage, lipid and protein synthesis, and detoxification (Hamed et al., ), for this reason, impairment liver function can lead to increase oxidative stress (Hamed et al., ). In our study, HFD increased the TBARS and carbonyls levels, whereas the NSE and UViSE extracts reduced these markers of oxidative damage; thus, ours extracts protect to the liver against oxidative damage, but unfortunately the effect of UViSE on protein oxidation was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, HFD increased the TBARS and carbonyls levels, whereas the NSE and UViSE extracts reduced these markers of oxidative damage; thus, ours extracts protect to the liver against oxidative damage, but unfortunately the effect of UViSE on protein oxidation was not significant. Likewise the strawberry has been used as hepatoprotective in liver injury by tetrachloride in rats, which is due to his anti‐apoptotic and antioxidant properties (Hamed et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was also evident from the histopathological evaluations. Other researchers have reported this pathology of lipid accumulation in the liver of animals following carbon tetrachloride administration [25][26][27]. The possible mechanism for this lipid accumulation may include: carbon tetrachloride-induced decrease in the secretion of lipids from the liver [28] as well as increase in the synthesis of lipids in the liver [29].…”
Section: Discussionmentioning
confidence: 99%
“…When an animal is exposed to an external source of free radicals (e.g., as a result of exposure to a toxic chemical) the animal's antioxidant defense mechanism steps in and tries to control the rate of deleterious bio-oxidation and molecular damage [31]. Table 5 Effect of aqueous extract of Dennettia tripetala on antioxidant enzyme activity and lipid peroxidation status in liver of rats exposed to carbon tetrachloride Table 6 Effect of aqueous extract of Dennettia tripetala on urea and creatinine concentration in the serum of rats exposed to carbon tetrachloride Several researchers have observed that the activities and expression of antioxidant enzymes such as SOD, catalase and glutathione peroxidase, drops drastically in the liver and kidney of animals exposed to an external source of free radicals compared to control animals [25,27,30,[32][33][34]. This may be explained by the fact that these radicals may inhibit (non-specifically) the synthesis as well as the activity of antioxidant enzymes in the liver and kidney at the DNA level and at the protein level respectively [31,[35][36][37].…”
Section: Discussionmentioning
confidence: 99%